Chemical Characterization of Two Botanicals from Genus Alternanthera - A. brasiliana (L.) Kuntze and A. paronychioides A. St.-Hil - Achintya Kumar Mandal; Rajesh Allu; Rajesh Chandran; Divya Kallingil Gopi; Sunil Kumar Koppala Narayana; Radha Prakasam; Shakila Ramachandran (Pharmacognosy Research, 2023)
Background: Traditional medicine has become part and parcel of the present era for the maintaining and preventing of ailments. Alternanthera brasiliana and Alternanthera paronychioides (Amaranthaceae) are widely used in traditional medicine. Ab is widely familiar as penicillin in Brazil. Ap is known to treat gout, hyperuricemia, rheumatic arthritis, nephritis etc. as folk medicine. The present study aims to compare standardization profiles for A. brasiliana and A. paronychioides. Materials and Methods: Sample Ab and Ap were collected and authenticated. Authenticated samples were subjected to powder microscopy, physico-chemical, phytochemical, HPTLC and HPLC fingerprint and PXRD analysis. Results: Powder microscopic investigations revealed the characteristic features for identification. Physico-chemical investigation revealed the slightly acidic nature of both plants. The phytochemical test showed the existence of phenol, terpenoids and steroids as major secondary metabolites in both species. Photo documentation, fingerprints and spectral comparison by HPTLC and fingerprints by HPLC validate the existence of similar compounds in both Ab and Ap. PXRD analysis revealed the variance of elements present in both species. Conclusion: Comparative physico-chemical, phytochemical and HPLC, HPTLC, and P-XRD instrumental analysis of A. brasiliana and A. paronychioides provides distinct features for identification.
Keywords: Amaranthaceae; chromatographic fingerprinting; Comparative standardization; HPLC; HPTLC; PXRD.